2007
DOI: 10.1101/gad.445307
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the σE stress response by DegS: how the PDZ domain keeps the protease inactive in the resting state and allows integration of different OMP-derived stress signals upon folding stress

Abstract: The unfolded protein response of Escherichia coli is triggered by the accumulation of unassembled outer membrane proteins (OMPs) in the cellular envelope. The PDZ-protease DegS recognizes these mislocalized OMPs and initiates a proteolytic cascade that ultimately leads to the E-driven expression of a variety of factors dealing with folding stress in the periplasm and OMP assembly. The general features of how OMPs activate the protease function of DegS have not yet been systematically addressed. Furthermore, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 33 publications
3
90
0
Order By: Relevance
“…Moreover, crystal structures of DegS ⌬PDZ closely resemble the active conformation of intact DegS (Fig. 1, B and C) and have a functional oxyanion hole (6,12). These results support an allosteric model in which the unliganded PDZ domain stabilizes the inactive protease domain conformation, whereas OMP peptide binding to the PDZ domain reduces or eliminates this inhibitory effect.…”
supporting
confidence: 70%
“…Moreover, crystal structures of DegS ⌬PDZ closely resemble the active conformation of intact DegS (Fig. 1, B and C) and have a functional oxyanion hole (6,12). These results support an allosteric model in which the unliganded PDZ domain stabilizes the inactive protease domain conformation, whereas OMP peptide binding to the PDZ domain reduces or eliminates this inhibitory effect.…”
supporting
confidence: 70%
“…Recent study showed that ligand binding to PDZ1 induces an allosteric activation of DegP (39). Similar PDZ-ligand-dependent activation has also been reported for DegS, a DegP homolog (9,10). RseP and DegP are similar in that they have tandem PDZ domains, but the roles of these domains appear to be different between these two enzymes.…”
Section: Discussionmentioning
confidence: 72%
“…3A). This finding suggests that the noncleavable ALE peptide might function as an allosteric activator like in the homologous DegS protease, where peptide binding to the PDZ domain triggers a series of conformational changes in the catalytic domain that stimulate peptidase activity (18,19). To explore further the activating effect of the ALE peptide, we preincubated DegP with saturating amounts of the potential activator and measured the rate of degradation of the ''poor'' SPM-FKGV-pNA substrate that lacks a C-terminal anchoring motif.…”
Section: Resultsmentioning
confidence: 99%
“…However, the nature of the allosteric activator is different and mirrors the degree of protease specificity. The DegS regulator is selectively activated by ligands with a XF C-terminal motif, a characteristic motif of the C termini of outer membrane proteins signaling the onset of folding stress (19). In contrast, a broad palette of peptide ligands with a rather unspecific XX C-terminal consensus can activate the housekeeping DegP protease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation